Using Web 2.0 technologies and collaborative work in teaching academic writing - Jekiel, Mateusz (My University, 2014)
Teaching academic writing to ESL learners can be a difficult task: students are usually unfamiliar with academic style, have difficulties in producing a structured piece of writing and get easily discouraged by an examoriented approach, having to use old school pen and paper with no access to technology. Indeed, the gap between everyday writing tasks and the exam is significant: access to online dictionaries, linguistic corpora and academic articles, as well as being able to work in groups using Web 2.0 technologies (e.g. Google Docs) is a standard in today's professional writing. However, most students are less techsavvy than it is presumed: they are generally unaware of practical web tools, use Google search ineffectively and obtain information from unreliable sources. Hence, the implementation of a more practical approach with the use of web technologies and collaborative assignments in the writing classroom should be considered by ESL teachers. Incorporating collaborative practices in higher education can be beneficial on many levels: students become more conscious of their work, profit from peer correction and compose better works in terms of language and structure (Storch 2005). Moreover, using Web 2.0 tools can be especially advantageous, as it promotes cooperation skills, provides a userfriendly environment for peer reviewing and prepares students for future careers in networking (Brodahl et al. 2011, Kessler et al. 2012). In the following preliminary research, I compared individual pen and paper compositions with collaborative online works written on the same topic by two groups of 20 students on a comparable level of language proficiency (CAE). One of the groups practiced in class how to use Google Docs and search for reliable information online. The results show that students working in groups via Web 2.0 tools 1) generate more complex ideas, 2) learn from each other, 3) compose better texts in terms of language and content, 4) raise their awareness of plagiarism, and 5) develop a positive attitude to collaborative work. Therefore, collaborative exercises and webbased tools should be subject to more academic research and become a part of the writing course for ESL students.
Paper presented at YLMP 2014
Keywords: collaborative writing; second language writing; computer-assisted language learning; Web 2.0